Studi Komparatif Dampak Gaya Mengajar Guru terhadap Keaktifan Pesertaa Didik pada Pembelajaran PPKn di Kelas Tinggi - Arbela Sekar Adinda; Hasna Mahira; Syifa’ Az-Zahro; Endrise Septina Rawanoko (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research is a qualitative research with a comparative study approach that aims to analyze the influence of differences in teachers' teaching styles on students' activeness in learning Pancasila Education in the high class of SD Negeri Losari, Surakarta. The main focus of this study is to compare the application of learning strategies in grades IV and V and their impact on student participation and engagement in learning activities. The research subjects included 20 students in grade IV, 18 students in grade V, and two classroom teachers. Research data was collected through observation of the learning process, interviews with teachers, and documentation of the implementation of learning activities. Data analysis is carried out qualitatively through data reduction, data presentation, and conclusion drawn. The results of the study showed that grade IV teachers applied interactive learning methods based on Problem Based Learning (PBL) and Understanding by Design (UbD) which utilized digital learning media such as PowerPoint and LKPD, thereby encouraging students to actively discuss, ask, and present the results of group work. Meanwhile, learning in class V is still centered on teachers with lecture methods and the use of whiteboard media and package books, so that student activity tends to be low. The findings of the study confirm that the variety of teaching styles and the use of innovative media have a significant influence on increasing student activity as well as a more dynamic and participatory classroom atmosphere.